Dare to take charge : how to live your life on purpose - Hatchett, Glenda (New York : Center Street, 2010)
Challenges readers to ask self-reflective questions to overcome doubt and difficult circumstances and discover their potential for grace and success.
1. How Dare You Not? -- 2. Bridging the Dream Gap -- 3. Hope and Joy -- 4. Victim or Victorious? -- 5. Find Purpose and Passion in All That You Do -- 6. Do the Best You Can with What You've Got -- 7. Recalculating Is Part of the Process -- 8. Get Real About Reality -- 9. Be True to Yourself -- 10. Guilt Can Paralyze You -- 11. Your Past Does Not Define Your Future -- 12. Opportunity Knocks. Will You Answer? -- 13. New Hope Road -- 14. Claim Your Healing -- 15. You Define You -- 16. Lifting As We Climb - - 17. Write Your Own Story.
Keywords: Goal (Psychology); Success; Self-realization.